Earning Management and Financial Performance in Real Estate Company in Indonesia: Earning Management and Financial Performance in Real Estate Company in Indonesia - Alfiandri, (Archives of Business Research, 2022)
Earning management is a practice by the management to convince the stakeholders and to maintain a firm reputation by modifying or manipulating financial statements. This practice brings positive and negative impacts to firm performance. Although earning management was allegedly made by the managers to enhance financial reporting strategies and provide a positive opinion of the business, this practice would reduce the quality of the financial statements. Such reasons as financial distress and high competition are the name of few that the management manipulates financial statements. In addition to this, the study examines the effect of earnings management towards return on asset and market value in the company in Indonesia. The quantitative method was used to measure variables of the study and the data was taken from real estate and property companies that listed on the Indonesian stock exchange. The study finds that two indicators of earning management namely, total accrual (balance sheet approach and cash flow approach) have a significant effect on return on asset and market value. In addition to this, neither increase nor decrease on balance sheet approach and cash flow approach give the effect on firm performance Thus, practice on earning management play roles to the firm performance. In addition to this, the study provides the insight of earning management practice in the company as the contribution of the study